Histomorphogenesis of the Chukar Partridge (Alectoris Chukar) Knee Joint - Tannaz Mir; Bahador Shojaei; Shadi Hashemnia (Negah Institute for Scientific Communication, 2015)
Introduction: There are differences in the pattern of the knee joint formation of the studied species. According to the small number of studies which focused chronologically on the avian knee histomorphogenetic events, its "morphogenetic pattern" is hard to be proposed. The present work was designed to identify the sequential events of the knee formation in the partridge embryo. Regarding to different incubation periods of the partridge and the chick embryos, it is interesting to know if sequential morphogenetic events of the knee joint formation of these two avian models will happen through corresponding days of incubation. Methods: In this study partridge (AlectorisChukar) embryos were used from day 5 to 23 of incubation. 5 ;mum thick sections were obtained sagittally and frontally from the knee region. The slides were stained with Hematoxylin-Eosin (HE), green Trichrome Masson (TM) and Alsian Blue-Van Gieson's (ABV) methods and studied by light microscope. Results: In the knee development of partridge we determined three layered interzone formation, joint cavitation and other morphogenetic events of the knee structures of the partridge. Conclusion: According to comparison of present results and other similar studies, it seems that birds and mammals follow different timely and sequential pattern of the knee formation.